EFL learners’ perceptions towards the active reading software as a learning tool to enhance reading comprehension - Khan, Imran; Ainol Haryati, Ibrahim; Asiah, Kassim; Khan, Raja Muhammad Ishtiaq (Open Access Publishing Group, 2020)
The present study endeavored to explore EFL students' perceptions regarding the acceptance and intervention of ARS in enhancing reading comprehension ability at Majmaah University, Saudi Arabia. The study engaged 30 male undergraduates of English major B.A program. For data collection, the study utilized a qualitative technique using semi-structured interviews and the interview questions were constructed based on the principles of Technology Acceptance Model (TAM) by Davis (1989). Active Reading Software (ARS) was employed as a technological tool for teaching reading comprehension. The treatment group received intervention from ARS for the duration of four weeks in the computer lab. Qualitative data obtained from the students' interviews were evaluated by means of thematic analysis using Braun and Clarke’s (2006) framework. The results of the thematic analysis pointed out five major themes considered to be the factors that influenced participants’ perceptions towards ARS as a learning tool for improving reading comprehension at the tertiary level. Findings of the present study offer essential implications for language instructors and educational institutions providing technology-integrated courses. Understanding the factors influencing the learners’ perceptions towards the adoption of technological tools in learning is significant for its success.